Densitometry of STR-PAGE for donor chimerism in acute leukemia’s: A simple method for routine use - Nayyar, Ayesha; Ahmed, Suhaib (Pakistan Journal of Medical Sciences, 2024)
Objective: To evaluate a PCR based method of polyacrylamide gel electrophoresis of short tandem repeats and its quantification for detecting donor chimerism after haematopoietic stem cell transplantation in acute leukaemias. Methods: The descriptive study was conducted at Genetic Resource Centre (GRC) Lab Rawalpindi from Feb 2018 - Nov 2020. A total of twenty patients with acute leukaemias having undergone HSCT were selected and assessed for the analysis of chimerism status. DNA extraction from the whole blood was done by chelex method and short tandem repeats were amplified by using conventional STR- PCR assay. Electrophoresis was carried out and 6% polyacrylamide gels were used for the resultant amplified DNA products and then followed by their densitometry. These patients had undergone HSCT from Pakistan Institute of Medical Science and Armed Forces Bone Marrow Transplant Centre. Results: The peaks in the PAGE densitometry represented the donor chimerism in all post transplant samples of the patients. Conclusion: Our study showed that densitometry of STR PCR PAGE is a useful and cheaper method for demonstration of donor chimerism in acute leukaemia patients having undergone HSCT. Hence this method can be a valuable option in the monitoring of chimerism status in these patients and therefore helps in preventing graft failure by fast and early treatment strategies for these patients. doi: https://doi.org/10.12669/pjms.40.5.9216 How to cite this: Nayyar A, Ahmed S. Densitometry of STR-PAGE for donor chimerism in acute leukemia’s: A simple method for routine use. Pak J Med Sci. 2024;40(5):875-878. doi: https://doi.org/10.12669/pjms.40.5.9216 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.